A Multidisciplinary Approach to Pretransplant and Posttransplant Management of Cystic Fibrosis–Associated Liver Disease. Issue 4 (20th March 2019) - Freeman, A. Jay; Sellers, Zachary M.; Mazariegos, George; Kelly, Andrea; Saiman, Lisa; Mallory, George; Ling, Simon C.; Narkewicz, Michael R.; Leung, Daniel H.
Abstract : Approximately 5%‐10% of patients with cystic fibrosis (CF) will develop advanced liver disease with portal hypertension, representing the third leading cause of death among patients with CF. Cystic fibrosis with advanced liver disease and portal hypertension (CFLD) represents the most significant risk to patient mortality, second only to pulmonary or lung transplant complications in patients with CF. Currently, there is no medical therapy to treat or reverse CFLD. Liver transplantation (LT) in patients with CFLD with portal hypertension confers a significant survival advantage over those who do not receive LT, although the timing in which to optimize this benefit is unclear. Despite the value and efficacy of LT in selected patients with CFLD, established clinical criteria outlining indications and timing for LT as well as disease‐specific transplant considerations are notably absent. The goal of this comprehensive and multidisciplinary report is to present recommendations on the unique CF‐specific pre‐ and post‐LT management issues clinicians should consider and will face.